2014
DOI: 10.1017/s0031182014000201
|View full text |Cite
|
Sign up to set email alerts
|

In vitro leishmanicidal activity of pyrazole-containing polyamine macrocycles which inhibit the Fe-SOD enzyme of Leishmania infantum and Leishmania braziliensis species

Abstract: The in vitro leishmanicidal activity and cytotoxicity of pyrazole-containing macrocyclic polyamines 1-4 was assayed on Leishmania infantum and Leishmania braziliensis species. Compounds 1-4 were more active and less toxic than glucantime and both infection rates and ultrastructural alterations confirmed that 1 and 2 were highly leishmanicidal and induced extensive parasite cell damage. Modifications in the excretion products of parasites treated with 1-3 were also consistent with substantial cytoplasm alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…It also showed poor selectivity against the Fe-SOD of the Leishmania species with respect to the CuZn-SOD of human erythrocytes. All these data seem to confirm some kind of relation between parasiticidal activity and inhibition of Fe-SOD, in accordance with results described in previous work (Sánchez-Moreno et al 2011, 2012 b ,c ; Navarro et al 2014). Fe-SOD inhibition could also, at another level, be related to the catabolic changes discussed above, since a mitochondrial malfunction, originating from the redox stress produced by inhibition of the mitochondrion-resident Fe-SOD enzyme (Kirkinezos and Moraes, 2001), should result in severe alteration of pyruvate metabolism and a consequent decrease in the production of succinate.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It also showed poor selectivity against the Fe-SOD of the Leishmania species with respect to the CuZn-SOD of human erythrocytes. All these data seem to confirm some kind of relation between parasiticidal activity and inhibition of Fe-SOD, in accordance with results described in previous work (Sánchez-Moreno et al 2011, 2012 b ,c ; Navarro et al 2014). Fe-SOD inhibition could also, at another level, be related to the catabolic changes discussed above, since a mitochondrial malfunction, originating from the redox stress produced by inhibition of the mitochondrion-resident Fe-SOD enzyme (Kirkinezos and Moraes, 2001), should result in severe alteration of pyruvate metabolism and a consequent decrease in the production of succinate.…”
Section: Resultssupporting
confidence: 92%
“…In light of these findings, we proceeded to evaluate the activity of series I–V towards L. braziliensis and L. infantum parasites, as significant representatives of species causing CL and VL, respectively. It was found that the tested compounds exhibited a behaviour closely related to that found in T. cruzi : good in vitro activity, low toxicity against mammalian cells and inhibition of Leishmania Fe-SOD (Sánchez-Moreno et al 2012 c ; Marín et al 2013; Navarro et al 2014). One point to highlight is that a noticeable structure-activity relationship was observed in the compounds studied in both the Leishmania and T. cruzi assays.…”
Section: Introductionmentioning
confidence: 91%
“…Tautomery can alter the skeleton of a given molecule, which in principle can be seen as a new distinct molecule with different complementarity to the target. Thus, Sanchez-Moreno et al studied the differences in activity against T. cruzi Fe-SOD enzyme of the possible tautomers of several imidazole derivatives [274][275][276][277][278].…”
Section: Tautomerism and Bindingmentioning
confidence: 99%
“…In this context, the antichagasic and leishmanicidal properties of some pyrazole-containing benzo[ g ]phthalazines (Sánchez-Moreno et al 2011, 2012 b ) and pyrazole-derived macrocyclic polyamines (Sánchez-Moreno et al 2012 c ; Navarro et al 2014) have been reported in the last years. It has been proposed that these compounds act as inhibitors of iron superoxide dismutase (Fe-SOD), essential for the parasites survival.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the complexing ability of these compounds has been related to anti-trypanosomatid activity. In fact, it has been pointed out (Sánchez-Moreno et al 2012 c ; Navarro et al 2014) that complexation of iron atom may modify the enzyme active site by dissociation of the metal ion, by changes in the coordination geometry or reducing the interaction between the two monomers of the enzyme.…”
Section: Introductionmentioning
confidence: 99%